SARS-CoV-2 vaccination of convalescents boosts neutralization capacity against Omicron subvariants BA.1, BA.2 and BA.5 and can be predicted by anti-S antibody concentrations in serological assays - Seidel, Alina; Hoffmann, Simone; Jahrsdörfer, Bernd; Körper, Sixten; Ludwig, Carolin; Vieweg, Christiane; Albers, Dan; von Maltitz, Pascal; Müller, Rebecca; Lotfi, Ramin; Wuchter, Patrick; Klüter, Harald; et al. (Frontiers in Immunology, 2023)
Background Recent data on immune evasion of new SARS-CoV-2 variants raise concerns about the efficacy of antibody-based COVID-19 therapies. Therefore, in this study the in-vitro neutralization capacity against SARS-CoV-2 variant B.1 and the Omicron subvariants BA.1, BA.2 and BA.5 of sera from convalescent individuals with and without boost by vaccination was assessed. Methods and findings The study included 313 serum samples from 155 individuals with a history of SARS-CoV-2 infection, divided into subgroups without (n=25) and with SARS-CoV-2 vaccination (n=130). We measured anti-SARS-CoV-2 antibody concentrations by serological assays (anti-SARS-CoV-2-QuantiVac-ELISA (IgG) and Elecsys Anti-SARS-CoV-2 S) and neutralizing titers against B.1, BA.1, BA.2 and BA.5 in a pseudovirus neutralization assay. Sera of the majority of unvaccinated convalescents did not effectively neutralize Omicron sublineages BA.1, BA.2 and BA.5 (51.7%, 24.1% and 51.7%, resp.). In contrast, 99.3% of the sera of superimmunized individuals (vaccinated convalescents) neutralized the Omicron subvariants BA.1 and BA.5 and 99.6% neutralized BA.2. Neutralizing titers against B.1, BA.1, BA.2 and BA.5 were significantly higher in vaccinated compared to unvaccinated convalescents (p<0.0001) with 52.7-, 210.7-, 141.3- and 105.4-fold higher geometric mean of 50% neutralizing titers (NT50) in vaccinated compared to unvaccinated convalescents. 91.4% of the superimmunized individuals showed neutralization of BA.1, 97.2% of BA.2 and 91.5% of BA.5 with a titer ≥ 640. The increase in neutralizing titers was already achieved by one vaccination dose. Neutralizing titers were highest in the first 3 months after the last immunization event. Concentrations of anti-S antibodies in the anti-SARS-CoV-2-QuantiVac-ELISA (IgG) and Elecsys Anti-SARS-CoV-2 S assays predicted neutralization capacity against B.1 and Omicron subvariants BA.1, BA.2 and BA.5. Conclusions These findings confirm substantial immune evasion of the Omicron sublineages, which can be overcome by vaccination of convalescents. This informs strategies for choosing of plasma donors in COVID-19 convalescent plasma programs that shall select specifically vaccinated convalescents with very high titers of anti-S antibodies.